The potential of cholinesterases as tools for biomonitoring studies with sharks: Biochemical characterization in brain and muscle tissues of Prionace glauca - Alves, Luís M. (2022)
Cholinesterases (ChE) are a family of enzymes that play an essential role in neuronal and motor functions. Because of the susceptibility of these enzymes to anticholinergic agents and to other contaminants, their activity is frequently used as biomarker in pollution monitoring studies. The three known types of ChE in fish are acetilcholinesterase (AChE), butyrylcholinesterase (BChE) and propionylcholinesterase (PChE). The presence of these enzymes in each tissue differs between species, and thus their usage as biomarkers requires previous enzyme characterization. Sharks, mostly acting as apex predators, help maintain the balance of fish populations performing a key role in the ecosystem. Blue sharks (Prionace glauca) are one of the most abundant and heavily fished sharks in the world, thus being good candidate organisms for ecotoxicology and biomonitoring studies. The present study aimed to characterize the ChE present in the brain and muscle of the blue shark using different substrates and selective inhibitors, and to assess the in vitro sensitivity of these sharks' ChE to chlorpyrifos-oxon, a metabolite of a commonly used organophosphorous pesticide, recognized as amodel anticholinesterase contaminant. The results suggest that the brain of P. glauca seems to contain atypical ChEs, displayingmixed properties of AChE and BChE, and that the muscle tissue seems to contain mainly AChE. In vitro exposures to chloropyrifosoxon inhibited blue shark's ChE in both tissues, the brain being the most sensitive tissue and therefore the most suitable for detection of exposure to low concentrations of anticholinergic compounds in the environment. This study indicates that ChE activity in blue sharks has the potential to be used as a sensitive and reliable biomarker in marine biomonitoring programs.